KORELASI DENSITAS PENDUDUK DAN PERSEBARAN KASUS COVID-19 DI KOTA MANADO - Tjoa, Savy C.N.; Rogi, Octavianus H.A.; -, Suryono (SPASIAL, 2021)
Covid-19 is a new disease that causes a serious pandemic disaster. In theory, transmission of infectious diseases is often facilitated by congested areas. This raises a question whether the density theory applies conceptually in Manado City, which is the capital as well as the main gateway with the largest population in North Sulawesi Province. Population density is one of the important indicators in identifying the spatial structure of a city. And going forward, it is very necessary to develop an ideal urban spatial structure and respond to a pandemic. The purpose of this study was to analyze the relationship between density indicators, both static and dynamic, and the distribution of Covid-19 in Manado City. The method used is quantitative-qualitative which consists of the origin-destination preference survey method as an identification of the movement pattern of the Manado City population which becomes the dynamic density and Pearson correlation as an analytical tool. The results showed that there was no correlation between population density on built-up land (static density) and the distribution of Covid-19 cases in Manado City. However, the results of the identification of the type of spatial structure of Manado City which tend to be mono-polycentric based on indicators of population movement (dynamic density) correlated with the distribution of existing cases. Especially for the trip to work, recreation, and to health facilities, it has a significant correlation coefficient with the increase in cases during the peak (first wave) Covid-19 in Manado City. Based on the research findings, the recommended spatial structure model to prevent and reduce problems arising from the pandemic is themodel Polycentric City.Keyword : Static Density, Dinamic Density, Covid-19, Pearson Correlation